Regional and urban‒rural differences in childhood growth trajectories and the role of family in China - Fang Tang; Minghe Zhou; Bo Li (Scientific Reports)
Abstract Children in urban and eastern regions tend to be taller and have higher body mass index (BMI) compared to those in rural and central-western regions, partially due to better family resources. We examined urban‒rural areas, regional differences in growth trajectories, focusing on family influences. Longitudinal data on 8542 children from the China Health and Nutrition Survey (1991–2015) were used. Random effects models assessed the mean height/BMI growth trajectories across different regions, urban–rural areas, and sexes within cohorts born in 1980–1989, 1990–1999, and 2000–2009. In the 1980–1989 cohort, before adjusting for family dietary structure, children from eastern regions were on average 3.3 cm taller than those from central-western regions at age 6. After adjustment, the height difference decreased to 2.44 cm. In the 2000–2009 cohort, the urban–rural BMI difference at age 6 was initially 0.53 kg/m2, which narrowed to 0.40 kg/m2 after adjusting for family socioeconomic factors. After adjusting for family environmental sanitation, the regional difference in the 2000–2009 cohort was attenuated by half before adjustment and was 0.44 kg/m2 after adjustment. Family factors significantly account for the regional and urban–rural disparities in height and BMI. These disparities were driven by the family resource environment, like dietary structure and sanitation. However, with China’s socioeconomic changes, broader socioeconomic factors, including household income and parental education, have become more influential.